SPECIALLY PROTECTED ENVIRONMENTAL AREAS X REGISTRATION IN REAL ESTATE OFFICE - Augusto de Souza Aguiar, Bruno (Journal of Interdisciplinary Debates, 2023)
Areas with special environmental protection designations have legal regulations to ensure biodiversity conservation and sustainable resource management. Among these areas are the Private Natural Heritage Reserves (RPPNs), Legal Reserves (RLs), and Environmental Easement Areas (ASAs). This study focuses on the importance of recording these zones in property registries at the Deed Offices. This practice centralizes crucial information about the property, including judicial and administrative aspects and obligations associated with the property, ensuring transparency and information for potential buyers and interested third parties. The employed methodology involved documentary research and systematic data analysis. It emphasizes the importance of intensifying the adoption of the concentration principle in property registration, through recording, to provide greater legal security, visibility, protection of areas, and to mitigate potential fraud. This study serves as a guide for registry professionals and the general public on the legal significance of recording in protected areas.